ANALISIS MEDAN LISTRIK YANG DIPRODUKSI OLEH PRELIMINARY BREAKDOWN PADA PETIR NEGATIF AWAN KE BUMI - Fadli Eka Yandra (Jurnal Civronlit Unbari, 2017)
The main objective of this thesis is to demonstrate the benefits of the analysis of Power Spectrum Density (PSD) to observe the change of the electric field at intermediate negative lightning cloud to ground (CG) and terminology-intermediate breakdown-leader (BIL) before turning the struck first. Analysis was done on data 74 occurrence of lightning in the city of Padang, with terminology BIL. Time domain analysis time – frequency of use applications Short Time Fourier Trasnform (STFT), then the results of the analysis time domain – frequency domain analysis compared with the time. The basis of the use of the STFT is the calculation of Spektogram.  Time domain analysis of results time – frequency domain analysis against the difference obtained by time, where for data with sampling rate 1 MS/s (low resolution) in the domain of time, does not happen much changes compared data with sampling rate 25 MS/s (high resolution), high resolution spectrum due to clearer spectrum amplitude frequency. Different the results of the calculation phase BIL with time domain data will look on the lightning with a time limit of occurrence of short or Intermediate phase on the value of the voltage E smaller, because it forms the lower wave recording-amplitudo, so can be seen clearly the difference phases of BIL is happening. Keyword: Preliminary Breakdown, Intermediate Duration, phase based on Power Spectrum Density BIL.